Gene Silencer Therapy in Transthyretin Amyloid Cardiomyopathy - Julian D. Gillmore; Yasuhiro Hamatani; Marianna Fontana; Muthiah Vaduganathan; Brian L. Claggett; Pablo Garcia-Pavia; Ahmad Masri; Francesco Cappelli; Martha Grogan; Caroline Morbach; Mathew S. Maurer; Scott D. Solomon (JAMA, 2026)
Importance Gene-silencing therapies reduce hepatic transthyretin (TTR) production and have been evaluated in phase 3 trials in TTR amyloid cardiomyopathy (ATTR-CM). However, differences in trial design and background therapies have limited assessment of the overall treatment effect and its consistency according to baseline TTR stabilizer use. Objective To assess the effect of TTR gene-silencing therapies in patients with ATTR-CM. Data Sources and Study Selection PubMed was searched through June 15, 2026, for randomized, placebo-controlled, phase 3 outcome trials of gene-silencing therapies in ATTR-CM. Data Extraction and Synthesis Two reviewers independently extracted data, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses ( PRISMA ) guideline. Fixed-effects meta-analysis estimated rate ratios (RRs) or hazard ratios (HRs) with 95% CIs. Main Outcomes and Measures The prespecified primary outcome was the composite of all-cause mortality and recurrent cardiovascular events. Secondary outcomes included all-cause mortality, cardiovascular death, time to first primary outcome, functional capacity (6-minute walk distance), and health status (Kansas City Cardiomyopathy Questionnaire–Overall Summary Score). Results A total of 2 studies (HELIOS-B and CARDIO-TTRansform) met the inclusion criteria and included 2086 patients with ATTR-CM. The studies included 1902 men with a median age of 77 years (range for HELIOS-B, 45-85 years; for CARDIO-TTRansform, 41-91 years). Gene-silencing therapy reduced the primary end point by 20% (RR, 0.80; 95% CI, 0.69-0.94; P = .006), with no heterogeneity between trials ( P for heterogeneity = .28). Gene-silencing therapy also reduced the risk of all-cause death (HR, 0.74; 95% CI, 0.61-0.91) and time to first all-cause death or cardiovascular events (HR, 0.77; 95% CI, 0.67-0.89) compared with placebo. Gene silencers preserved 6-minute walk distance (placebo-corrected difference, +22.2 m; 95% CI, 14.3-30.0) and Kansas City Cardiomyopathy Questionnaire–Overall Summary Score (+4.5; 95% CI, 2.7-6.2), with no evidence of between-trial heterogeneity. Treatment effects on primary end points differed according to baseline stabilizer use, with significant benefits observed among patients not receiving background stabilizer therapy (RR, 0.69; 95% CI, 0.57-0.85) and no significant incremental benefit observed for those receiving concomitant stabilizer at baseline (RR, 0.97; 95% CI, 0.77-1.23; P for heterogeneity = .03). Similar heterogeneity was observed for functional capacity and health status. Conclusions and Relevance The findings from this meta-analysis support TTR gene silencing for ATTR-CM. The attenuated benefit observed for patients receiving concomitant TTR stabilizer therapy may reflect residual differences in case mix, disease duration, or magnitude of TTR suppression or a true ceiling on additional benefit of gene silencing in the setting of background TTR stabilization. Trial Registration PROSPERO registration: CRD420261421656 . ClinicalTrials.gov Identifier: HELIOS-B, NCT04153149 ; and CARDIO-TTRansform, NCT04136171